PERBEDAAN TEKANAN DARAH SEBELUM DAN SESUDAH PEMBERIAN AIR KELAPA HIJAU (Cocos nucifera Linn) PADA TENAGA KERJA BAGIAN PENGECATAN DI KAROSERI X SEMARANG - Fitriati, Ika; Setiani, Onny; Darundiati, Yusniar Hanani (Jurnal Kesehatan Masyarakat (Undip), 2016)
The painting section is one of the employees who are at risk for to loaded heavy metals exposure. Karoseri is one of the automotive industries that high concentrate of lead in the industry. It may increase systolic and diastolic blood pressure. The one way to decrease blood pressure is consuming green coconut water. The aimed of this research was to determine differences in blood pressure before and after being giving green coconut water to the labors at the painting section in Karoseri X Semarang. The design of this research used quasi experiment with the design research the one group pretest posttest design. The population in this study was all the labors at the painting section in Karoseri X Semarang and this amounts 32 respondents using purposive sampling method. The analysis of this research used unvariate and bivariate analysis using a paired t-test and wilcoxon. The average systolic and diastolic blood pressure before being giving of green coconut water are 124.91 mmHg and 75.16 mmHg, while after being giving of green coconut water supplementation are 123.25 mmHg and 73.22 mmHg. The results of this research showed no differences in the blood pressure before and after green coconut water supplementation (Cocos nucifera Linn) to the labors of the painting section in Karoseri X Semarang, the systolic pressure (p 0,467> α 0.05) and diastolic (p 0.480> α 0.05). The blood pressure is influenced by several conditions as follows age, gender, diet, emotions, history of disease, Pb levels in the blood, smoking habits, nutritional status, and etc.